Polymeric materials in dentistry - Sideridou, Irini D. (Dental science, materials and technology series., 2010)
The use of polymers for dental purposes started with the invention of vulcanized rubber. The development of the dough technique made it possible to use polyacrylates in dentistry. The physical and mechanical properties of the cured base denture can be optimized by the proper selection of an initiator, plasticizer, pigment and cross-linking agents (di- or trifunctional methacrylates) The developing of the redox initiators for the polymerization of methacrylates at room temperature made possible the direct application of these materials as filling resins. This book has been written in an effort.